Red and near‐infrared light‐activated photoelectrochemical nanobiosensors for biomedical target detection (2024)
ABSTRACT: Photoelectrochemical (PEC) nanobiosensors integrate molecular (bio)recognition elements with semiconductor/plasmonic photoactive nanomaterials to produce measurable signals after light-induced reactions. Recent advancements in PEC nanobiosensors, using light-matter interactions, have signifcantly improved sensitivity, specifcity, and signal-to-noise ratio in detecting (bio)analytes. Tunable nanomaterials activated by a wide spectral radiation window coupled to electrochemical transduction platforms have further improved detection by stabilizing and amplifying electrical signals. This work reviews PEC biosensors based on nanomaterials like metal oxides, carbon nitrides, quantum dots, and transition metal chalcogenides (TMCs), showing their superior optoelectronic properties and analytical performance for the detection of clinically relevant biomarkers. Furthermore, it highlights the innovative role of red light and NIR-activated PEC nanobiosensors in enhancing charge transfer processes, protecting them from biomolecule photodamage in vitro and in vivo applications. Overall, advances in PEC detection systems have the potential to revolutionize rapid and accurate measurements in clinical diagnostic applications. Their integration into miniaturized devices also supports the development of portable, easy-to-use diagnostic tools, facilitating point-of-care (POC) testing solutions and real-time monitoring.